A new subspecies of Carabus (Archiplectes) edithae Reitter, 1893 from Caucasus (Coleoptera: Carabidae) - Obydov, Dmitry (Acta entomologica slovenica (Ljubljana), 2010)
A series of specimens of Carabus (Archiplectes) edithae Reitter, 1893 was collected in the Caucasus (Karachai-Cherkessian Region, Abishira-Akhuba Mountains). The geographically most adjacent subspecies of Carabus edithae to the collected specimens is Carabus edithae exedithae Gottwald, 1985. The collected specimens differ from this and other subspecies by many features andrepresent a new subspecies, Carabus (Archiplectes) edithae miloslavskii ssp. n., which is described in this paper and which most probably is restricted to the Abishira-Akhuba Mountains. Diagnostic characters are given.
Keywords: entomologija; hrošči; Kavkaz